ANALISIS PERBANDINGAN MODEL TAFFLER, GROVER DAN ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN - Shara Agustin Anggi Yana; Tri Widodo; Maria Entina Puspita (UNPERBA, 2026)
This study aims to determine bankruptcy prediction using the Taffler, Grover, and Zmijewski models for food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This study is a quantitative study using secondary data published by the Indonesia Stock Exchange. The research sample consisted of 20 companies. The data collection method used documentation methods with data analysis of bankruptcy prediction calculations using the Taffler, Grover, and Zmijewski models. The results showed that the Taffler method categorized 16 companies as not experiencing potential bankruptcy and 4 companies as having potential bankruptcy. The Grover model categorized 19 companies as not experiencing potential bankruptcy and 1 company as having potential bankruptcy. The Zmijewski model categorized 19 companies as not experiencing potential bankruptcy and 1 company as having potential bankruptcy. Of the three bankruptcy analysis models, the Taffler model was considered superior in predicting bankruptcy compared to the other methods. This demonstrates the importance of corporate transparency in presenting complete annual reports, including providing calculations of company bankruptcy predictions so that investors can analyze and use them as evaluation material before investing. Companies showing signs of bankruptcy can still consider and develop their financial activities, as well as introduce new or interesting ideas to help the company grow and avoid the risk of bankruptcy.